Elucidation of the Mechanism of Silver‐Catalyzed Inverse Electron‐Demand Diels‐Alder (IEDDA) Reaction of 1, 2‐Diazines and Siloxy Alkynes. Issue 1 (21st October 2019) - Avcı, Öyküm Naz; Catak, Saron; Dereli, Büşra; Aviyente, Viktorya; Dedeoglu, Burcu
Abstract: Density functional theory (DFT) calculations were utilized to reveal the effect of highly efficient transition metal catalysis in inverse electron demand Diels‐Alder (IEDDA) reactions. The silver‐catalyzed IEDDA reactions of 1, 2‐diazines and siloxy alkynes were investigated to highlight the effect of the catalyst and its mode of action. Two different reaction pathways, concerted and stepwise, were explored as well as the uncatalyzed reaction. Computations elucidate the details of the highly efficient Ag catalyst in IEDDA reaction, and are consistent with previous experimental studies. The mode of action for the catalyst is fully revealed and its specific effect on the regioselectivity/specificity of the reaction is established. Abstract : Mechanistic investigation : DFT calculations demonstrated that the silver catalyst efficiently enhances the inverse electron demand Diels‐Alder reaction of phthalazines with siloxy alkynes. The catalyst shifts the reaction from a concerted [4+2] cycloaddition to a stepwise ionic mechanism by lowering the reaction barrier significantly.